Antropoanalisi e cambiamento formativo. Nota su L. Binswanger - Mannese, Emiliana (Studi sulla Formazione/Open Journal of Education, 2014)
The theme of this brief note is tied to the focal point of my research, the scientific formative processes, and more in general to a certain approach of clinical pedagogy. I set out to analyze Biswanger’s existential analysis, that focuses on the human and the formative processes tied to interpersonal and educational activities, each one’s personal life story and processes of identity building.